A Comprehensive Guide to Socialization Strategies for Preventing Bullying Among Students in Schools - Herman, Herman; Marbun, Yanty Maria Rosmauli; Sinurat, Bloner; Manurung, Rolan; Berlien, Richard; Tannuary, Arwin; Silalahi, Tiodora Fermiska; Purba, Ridwin; Rumapea, Elina Lulu; Rambe, Kartina Rahmadhani; Girsang, Semaria Eva Elita (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The objective of this socialization was to socialize and give a comprehensive guide to the students in preventing bullying among students at school. As we know that nowadays bullying is always one of the hottest topics happening not only in Indonesia but also in some other schools in other countries in the world. Schools always try their best to draw up an official strategy in dealing with that problem. The participants in this program were the students of SMP Methodist Pematangsiantar located on Jalan Pane no. 34 in Pematangsiantar city. The socialization was held during the school environment introduction activities (PLS) on 15-16 July 2024. The results of this socialization were the students were given a comprehensive guide to prevent the bullying among students at school since the students were from different background, race, ethnics, and so on. The socialization process was initiated by analyzing the issue of bullying in schools, including its various forms, the effects on both victims and aggressors, the social influences that contribute to the problem, and the need for preventative measures tailored to the developmental needs of elementary, middle, and high school students. The discussion then delved into two theoretically grounded approaches for creating and implementing socialization strategies: the Pro-Social Developmental Guidance Model and the Social-Ecological Intervention Model. For each approach, strategies to evaluate, develop, implement, and sustain socialization strategies were identified, along with suggestions for integrating them into a cohesive approach. The guide also provides recommended antibullying strategies and programs, as well as an extensive list of references. This resource is designed to aid educators and others in their efforts to prevent bullying in schools.